Literature Review: The Relationship of Knowledge and The Selection of Long-Acting Contraceptive Methods - Tatik Dwiyani; Raisyah Ansakawirus; Mutiara Ayu Muthitulsalimah; Agus Rahmadi (STIKes Patria Husada Blitar, 2023)
The participation or involvement of Birth control program acceptors in selecting and using long- acting contraceptive methods (LACMs) in Indonesia still needs to be higher. The factors contributing to the minimal participation of KB acceptors in the selection or use of LACMs include the low level of knowledge among acceptors regarding the use of LACMs. The objective of the study was to explain the relationship between KB acceptors' knowledge and the selection of LACMs. This literature review used a systematic literature review of 10 articles related to the topic, which have been screened. Ten journals that had been selected say that all agree that there is a relationship between knowledge and LACMs. According to the researcher and the data obtained, it could be concluded that there was a match between the researcher's literature review results and current theory, as well as previous research results